ISOTRETINOIN INDUCED PSYCHOTIC SYMPTOMS - Tatyana Telbizova; Svetlin Varbanov (Peytchinski Publishing, 2023)
Isotretinoin is an effective treatment for severe and resistant forms of acne. It has proven potential for inducing dose-dependent psychiatric side effects, especially in some vulnerable groups of patients. Objective: The aim of the present article is to report a case of a 22-year-old woman with a family history of schizophrenia who was diagnosed with acne. After unsuccessful antibiotic treatment of acne, a panic disorder accompanied by depressive symptoms manifested. Isotretinoin 20 mg/day was used as а second step of the dermatological treatment for a period of four months, along with psychotropic treatment for panic disorder - sertraline 50 mg/day and flupentixol 1,5 mg/day. When the dose of Isotretinoin was increased to 40 mg/day, paranoid delusions occurred. The manifestation of psychotic symptoms required discontinuation of all medications and initiation of antipsychotic therapy with quetiapine. The psychotic symptoms completely disappeared when the dose of quetiapine was increased to 300 mg/day. Conclusion: The presented case emphasizes the need for increased vigilance about the manifestation of psychiatric symptoms, especially in patients with a family history, current or past medical history of mental disorder. In such cases, consultation with a psychiatrist before starting treatment with Isotretinoin is recommended in order to better clarify the benefits and the risks of the treatment. The endogenous origin of the psychosis was discussed in the differential diagnostic plan, which requires long-term monitoring of the mental state.